Correction: Gut microbiota can utilize prebiotic birch glucuronoxylan in production of short-chain fatty acids in rats. Issue 8 (5th April 2022) - Kynkäänniemi, Emma; Lahtinen, Maarit H.; Jian, Ching; Salonen, Anne; Hatanpää, Timo; Mikkonen, Kirsi S.; Pajari, Anne-Maria
Abstract : Correction for 'Gut microbiota can utilize prebiotic birch glucuronoxylan in production of short-chain fatty acids in rats' by Emma Kynkäänniemi et al., Food Funct., 2022, 13, 3746–3759, DOI: ; 10.1039/D1FO03922A .